LIP BALM PREPARATION FORMULATION CORIANDRUM LEAF EXTRACT (CORIANDRUM SATIVUM L.) AS A MOUSTURIZING LIPS* - Wulandari, Suci; Hasanah Fitria; Siti Wahyuni (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Leaf coriander (Coriandrum sativum L.) known own activity high antioxidants Lip balms is Wrong One preparations pharmaceutical form product functional beauty For help increase humidity on lips. Leaf coriander can made as substance active addition on lip balm formulas. it become reason use lip balms in study this. Study This aim For know is extract leaf coriander (Coriandrum sativum L.) can formulated become preparations lip balms And For know difference variation concentration extract leaf coriander (Coriandrum sativum L.) can influential as moisturizer on preparations lip balms Manufacturing process extract ethanol leaf coriander with method maceration use solvent 96% ethanol. preparation lip balms made in 4 formulas viz each with concentration extract leaf coriander 0% (F1), 5% (F2), 10% (F3), and 15% (F4). Testing to preparations lip balms covers test homogeneity , pH test , test stability for 4 weeks, test irritation , and test humidity to lips volunteer use tool skin analyzer with the parameters being measured covers moisture (water content). Maintenance done during four Sunday with use lip balms every a week once. Results study show that all preparations lip balms characteristic homogeneous , pH 7, shape , color , and the smell stable during storage And No irritate skin. Results measurement humidity show that lip balms extract ethanol leaf coriander 15% can increase the most moisture (water content). Extract ethanol leaf coriander (Coriandrum sativum L.) 15% in preparations lip balms more Good in increase moisture (water content) compared with extract ethanol leaf coriander 0%, 5% and 10%. Lip balms comparison show activity more moisture (moisture content). Good compared to with lip balms extract ethanol leaf coriander 15%.